Model Determinan Minat Beli Produk Kecantikan di Kota Surakarta: Analisis Peran Kualitas Produk, Persepsi Harga dan Digital Marketing - Shella Savita Ramadhani; Bangun Prajadi Cipto Utomo; Nur Hadi (STIE AUB Surakarta, 2026)
The Indonesian cosmetics market has experienced rapid growth lately, resulting in more intense competition among beauty firms. This research seeks aims to investigate how product quality, price, and digital marketing influence consumers' purchase intentions for Wardah cosmetics in Surakarta. This study employed a quantitative survey method. The participants included 100 female individuals aged fifteen years or older. The information gathered through a survey was examined using multiple linear regression. The results indicate that price, online advertising, and product quality have a significant and positive effect on purchase intention. Research indicated that the quality of a product significantly affects consumers' likelihood to buy. The findings suggest that enhancing product quality, keeping prices competitive, and optimizing digital marketing strategies can boost consumers' intention to purchase Wardah beauty products in Surakarta.